2004
DOI: 10.1007/s00535-003-1282-9
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology and expression of Ki-67 and cyclooxygenase-2 in childhood Helicobacter pylori gastritis

Abstract: H. pylori-infected children, suggestive of the early phase of infection, exhibit increased gastric epithelial cell proliferation, increased COX-2 expression, and other pathobiologic features that may contribute to gastric carcinogenesis. These results have clinical significance for the early introduction of eradication of H. pylori infection in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…However, other studies have reported a significant incidence of gastric atrophy (42%-55%) and intestinal metaplasia (13%-21%) in children (11,14) . Interestingly, a higher incidence of atrophic gastritis has been observed in children from countries with high incidence of gastric cancer (20) .…”
Section: Discussionmentioning
confidence: 89%
“…However, other studies have reported a significant incidence of gastric atrophy (42%-55%) and intestinal metaplasia (13%-21%) in children (11,14) . Interestingly, a higher incidence of atrophic gastritis has been observed in children from countries with high incidence of gastric cancer (20) .…”
Section: Discussionmentioning
confidence: 89%
“…However, one study reported relatively high prevalence of gastric atrophy and low-grade intestinal metaplasia in H. pylori -infected children compared to uninfected children [ 18 ].…”
Section: Histopathologic Findings In H Pylori -Infected Childrenmentioning
confidence: 99%
“…Half of the global population is infected by HP [6]. Chronic inflammation with H. pylori infection leads to mucosal atrophy and intestinal metaplasia, conditions that are believed to be precursors of gastric cancer [6,12]. The development of gastric cancer has been shown to be a multi step process, ranging from chronic gastritis to atrophy, intestinal metaplasia, dysplasia and finally gastric cancer [9].…”
Section: Introductionmentioning
confidence: 98%
“…Half of the global population is infected by HP [6]. Chronic inflammation with H. pylori infection leads to mucosal atrophy and intestinal metaplasia, conditions that are believed to be precursors of gastric cancer [6,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation